2022
DOI: 10.3390/children9020239
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Phenotype and Dysexecutive Syndrome of Preterm Children: Comorbidity or Trigger? An Update

Abstract: Premature birth is a worldwide public health priority. One in ten children is born before 37 weeks of gestational age and, in developed countries, survival rates without major neonatal morbidity are increasing. Although severe sequelae associated with these births have decreased, their neurobehavioral difficulties, often associated in multiple fields, remain stable but still widespread. These neurobehavioral difficulties hamper the normal development of academic achievements and societal integration and intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 170 publications
0
5
0
Order By: Relevance
“…In particular they are likely to have a lower total intelligence quotient (FSIQ) than that of the general population 23 . However, in cohorts of premature infants an FSIQ threshold close to a low mean (as assessed by WPPSI‐IV) is generally considered ‘normal’, although the observed performances are the result of complex processes involving multiple intellectual and non‐intellectual characteristics, such as attention, emotions, motivation, planning of movements and executive functions 10 . The multicentric and national nature of the recruitment of the EPIPAGE2 cohort provided a good representation of the various treatments occurring in 2011 in France.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular they are likely to have a lower total intelligence quotient (FSIQ) than that of the general population 23 . However, in cohorts of premature infants an FSIQ threshold close to a low mean (as assessed by WPPSI‐IV) is generally considered ‘normal’, although the observed performances are the result of complex processes involving multiple intellectual and non‐intellectual characteristics, such as attention, emotions, motivation, planning of movements and executive functions 10 . The multicentric and national nature of the recruitment of the EPIPAGE2 cohort provided a good representation of the various treatments occurring in 2011 in France.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other authors have shown that, after 2 years, neurodevelopmental difficulties were more marked in MC twins compared with DC twins 8,9 . A neurodevelopmental assessment is necessary at a later age (school age) because it is more reliable 10 …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Subsequent desynchronization of activity mirrors the increasing influence of sensory inputs shaping neuronal activity (Toyoizumi et al, 2013 ). Notably, due to different types of processed information and timelines of circuit assembly, different areas and functions exhibit distinct sensitive periods of maturation, e.g., the human visual system being particularly sensitive during the first few years of life, while language acquisition is sensitive during the first year after birth (Wiesel, 1982 ; Daw, 1998 ; Anderson and Reidy, 2012 ; Friedmann and Rusou, 2015 ; Gire et al, 2022 ). Similarly, in rodents, experience shapes synaptic circuits of visual and auditory systems during periods of enhanced plasticity, following eye/ear opening (Lehmann and Löwel, 2008 ; Rinaldi Barkat et al, 2011 ).…”
Section: Early Patterns Of Neuronal Activity In Schizophrenia and Aut...mentioning
confidence: 99%